2012
DOI: 10.2169/internalmedicine.51.8027
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Combined NT-pro-BNP Levels and NIHSS Scores in Patients with Acute Ischemic Stroke

Abstract: Objective Determining the prognoses of patients with acute ischemic stroke is difficult. Therefore, the aim of this study was to evaluate whether the combined assessment of plasma N-terminal pro-brain natriuretic peptide (NT-pro-BNP) and the National Institutes of Health Stroke Scale (NIHSS) variables is relevant to the prognosis of patients with acute cerebral ischemic infarction in-hospital. Methods We enrolled 122 patients who were within three days of onset of acute ischemic stroke. We measured the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 27 publications
1
38
3
2
Order By: Relevance
“…Together with other cardiac biomarkers such as troponin25 and B‐type natriuretic peptide (BNP),26, 27 our data highlight overlapping injury responses that occur following both cerebrovascular and cardiovascular injury. There are several possible interpretations of our findings in this context.…”
Section: Discussionmentioning
confidence: 55%
“…Together with other cardiac biomarkers such as troponin25 and B‐type natriuretic peptide (BNP),26, 27 our data highlight overlapping injury responses that occur following both cerebrovascular and cardiovascular injury. There are several possible interpretations of our findings in this context.…”
Section: Discussionmentioning
confidence: 55%
“…Emboli originating from heart atria can cause occlusion of major cerebral arteries, resulting in extensive cerebral infarction that is accompanied by severe neurological impairment. Indeed, it has been shown that greater BNP values correlate with a greater ischemic infarction volume on head CT [7]. On the other hand, hemorrhagic stroke is often due to rupture of the small perforating arteries that are damaged by long-standing arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence also suggests that NT-proBNP is released in response to brain damage and thus can be a valuable biomarker in cerebrovascular disease. For example, it has been shown that in acute stroke patients greater NT-proBNP serum concentrations are associated with greater clinical stroke severity, greater short-term and long-term mortality rates, and worse functional outcomes [4,5,6,7,8]. NT-proBNP has been shown to predict stroke-related mortality better than indexes of clinical stroke severity [4,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors used same combination of plasma NT-proBNP and NIHSS score in assessing in-hospital deaths: patients with NT-proBNP levels > 1583 pg/ml and NIHSS>12,5 on admission had a higher mortality rate (12) In another study (13), BNP plasma levels were higher among patients who deteriorated , BNP level being an independent predictor of neurological worsening and death in the acute phase after stroke.…”
mentioning
confidence: 99%